Treatment of type 2 diabetes and stress using neuro-emotional technique: case report - Bablis, Peter; Day, Ryan R.; Pollard, Henry (Frontiers in Endocrinology, 2024)
This case report presents a novel, non-pharmacological treatment of Type 2 Diabetes in a 46-year-old male, demonstrating improvements in blood chemistry and psychometric markers after 8 treatments using a Mind-Body Intervention (MBI) called Neuro-Emotional Technique (NET).The patient presented with a diagnosis of Type 2 Diabetes (T2D), pain, psychosocial indicators of stress and anxiety, and a score of 4 on the ACE-Q (Adverse Childhood Experiences Questionnaire) that is consistent with a predisposition to chronic disease and autoimmune disorders. Glucose levels for this patient were above normal levels (typically between 10-15mmol/L where optimal range is between 4-10mmol/L) for at least two months prior to the 4-week NET intervention period, despite the standard use of conventional antidiabetic medications (insulin injections).The patient exhibited numerous indictors of chronic stress that were hypothesised to be underlying his medical diagnosis and a series of 8 NET treatments over a period of 4 weeks was recommended. Psychometric tests and glucose measurements were recorded at baseline (prior to treatment), 4 weeks (at the conclusion of treatment) and at 8 weeks (4 weeks following the conclusion of treatment). Results show that glucose levels were reduced, and self-reported measures of depression, anxiety, stress, distress and pain all decreased from high and extreme levels to within normal ranges after 4 weeks, with ongoing improvement at 8 weeks.McEwen described the concept of allostatic load and the disruptive effects that cumulative stress can have on both mental and physical health. It is hypothesized that NET reduces allostatic load thereby fortifying homeostasis and the salutogenic stress response mechanisms involved in recovery from chronic illness, possibly via the Psycho-Immune-Neuroendocrine (PINE) network. Further studies with larger sample sizes are required to establish whether these results could be extrapolated to a wider population, however the results of this case suggest that it may be beneficial to consider co-management of T2D with an MBI such as NET.